STRATEGI PENGEMBANGAN WISATA TAMAN BUDAYA LIMBOTO DI KECAMATAN LIMBOTO KABUPATEN GORONTALO (Development Strategy of Cultural Park Tourism in Limboto District, Gorontalo Regency) - Yolanda Pinky Pande; Charles L. Ngangi; Melissa L. G. Tarore (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2022)
The aim of this research is to find out or analyze how the Limboto Cultural Park Tourism Development Strategy in Limboto District, Gorontalo Regency is. The research was conducted from October 2021 to December 2021Â The data used in this research are the primary and secondary data. then analyzed descriptively.The results showed that the Limboto Cultural Park Tourism was in quadrant I, which means a very favorable condition. Limboto Cultural Park Tourism has the power to take advantage of business opportunities. The strategy used in this condition is to support significant growth (Growth oriented strategy).